GEOCHEMISTRY OF VOLCANIC ROCKS OF THE BALEENDAH AREA AND SURROUNDINGS, BANDUNG REGENCY, WEST JAVA - Ikhram, Rinaldi; Ranuwijaya, Emir Sulaiman; Fachrudin, Kurnia Arfiansyah (Fakultas Teknik Geologi Universitas Padjadjaran, 2026)
The Baleendah area, Baleendah District, Bandung Regency, West Java, contains andesitic-dacitic volcanic rocks produced during the second eruptive phase of Baleendah Volcano ( 2.8–3.2 Ma). Major-oxide XRF analyses of four representative samples (ESR 02, ESR 14, ESR 18, ESR 22) yield SiO2 contents of 57.6–63.3 wt.%, classifying the rocks as andesite on the Total Alkali–Silica diagram. The FeOt/MgO vs. SiO2 diagram and AFM ternary diagram both place the samples within the tholeiitic series field; ESR 14 is transitional with the highest FeOt/MgO ratio of 9.45. Harker variation diagrams reveal systematic decreases in Al2O3, CaO, MgO, and FeOt with increasing SiO2, consistent with fractional crystallisation of plagioclase, pyroxene, and Fe–Ti oxides. Compared to the older Pliocene calc-alkaline suite from the Southern Bandung area (samples KRM and CPN), the ESR samples show lower MgO, CaO, Sr, V, and Co concentrations alongside higher FeOt/MgO ratios, indicating a more iron-enriched, more evolved magma. The tholeiitic character, elevated FeOt/MgO, and depleted compatible element concentrations collectively point to advanced fractional crystallisation under relatively low oxygen fugacity within a shallow crustal magma chamber beneath the Baleendah volcanic system.